Tele-Nursing: The Future of Remote Care for Healthcare Efficiency and Accessibility - Asbath Asbath; Kaito Tanaka; Yui Nakamura (Yayasan Adra Karima Hubbi, 2025)
The growing demand for healthcare services, coupled with the global shortage of healthcare professionals, has led to a need for innovative solutions to improve care efficiency and accessibility. Tele-nursing, a remote healthcare delivery model, has emerged as a promising solution to address these challenges. This study aims to explore the potential of tele-nursing in enhancing healthcare delivery, focusing on its role in improving efficiency and expanding access to care. The research employs a mixed-methods approach, combining qualitative interviews with healthcare professionals and quantitative analysis of patient outcomes from tele-nursing programs. The findings suggest that tele-nursing has the potential to reduce hospital readmissions, increase patient satisfaction, and improve chronic disease management. Furthermore, tele-nursing has proven effective in providing care to underserved populations, particularly in rural and remote areas, where access to healthcare services is limited. The study concludes that tele-nursing can play a pivotal role in shaping the future of healthcare by offering a more efficient and accessible alternative to traditional in-person care. However, challenges such as technology access, training, and regulatory issues must be addressed to ensure the successful integration of tele-nursing into healthcare systems.